Covid-19: Narasi Anti Hoaks Tentang Covid-19 di Media Sosial (Studi Kasus pada Akun Instagram @tempo.cekfakta) - Fauziah Muslimah (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
The spread of hoaxes and misinformation on social media coincides with the spread of the Covid-19 virus in Indonesia, even the world. Not infrequently, hoaxes that are trusted by the public cause new problems, apart from the health and economic sectors which cause a pandemic that is detrimental to the community. Therefore, the joint role of various parties needs to be done to educate the public and filter out information that is not yet clear. One of them was carried out by the Instagram account @tempo.cekfact as part of the Tempo.co mass media. This study discusses the use of Instagram accounts as social media to spread anti-hoax campaigns, especially related to the spread of the Covid-19 Virus. Using a case study method and a qualitative approach, this study documented photos and written texts from posts managed by the Tempo fact checker. The result of this research is that the Instagram account @tempo.cekfact is a breath of fresh air for anti-hoax actions on social media. Tempo.co.co.id in a national mass media ensures that the service is not only to convey information, but also to educate the public by being present on Instagram social media to filter out videos or photos that are not clear. Through the content of “facts or hoaxes” and campaigns through hashtags/hashmarks, Tempo's fact checker displays data and facts from various detailed sources to educate the public that the news is wrong, wrong or untrue.